2022
DOI: 10.1038/s41598-022-11606-w
|View full text |Cite
|
Sign up to set email alerts
|

Gaseous NO2 induces various envelope alterations in Pseudomonas fluorescens MFAF76a

Abstract: Anthropogenic atmospheric pollution and immune response regularly expose bacteria to toxic nitrogen oxides such as NO• and NO2. These reactive molecules can damage a wide variety of biomolecules such as DNA, proteins and lipids. Several components of the bacterial envelope are susceptible to be damaged by reactive nitrogen species. Furthermore, the hydrophobic core of the membranes favors the reactivity of nitrogen oxides with other molecules, making membranes an important factor in the chemistry of nitrosativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…PQS is an essential mediator of the shaping of the population structure of P. aeruginosa and of its response to and survival in stress conditions. [ a Myriam et al, 2022; b Chautrand et al, 2022; c Mitchell and Silhavy, 2019; d Hajiagha and Kafil, 2023; e Deuerling et al, 2019; f Hamza et al, 2023; g Coggan and Wolfgang, 2012; h Marsden et al, 2016; i Schuster and Greenberg, 2007, j Häussler and Becker, 2008, k Xu et al, 2020; l Fazeli-Nasab et al, 2022]…”
Section: Discussionmentioning
confidence: 99%
“…PQS is an essential mediator of the shaping of the population structure of P. aeruginosa and of its response to and survival in stress conditions. [ a Myriam et al, 2022; b Chautrand et al, 2022; c Mitchell and Silhavy, 2019; d Hajiagha and Kafil, 2023; e Deuerling et al, 2019; f Hamza et al, 2023; g Coggan and Wolfgang, 2012; h Marsden et al, 2016; i Schuster and Greenberg, 2007, j Häussler and Becker, 2008, k Xu et al, 2020; l Fazeli-Nasab et al, 2022]…”
Section: Discussionmentioning
confidence: 99%
“…Although the microbiome within all tested groups was reduced, the Gram-negative bacteria appeared to be most susceptible to the PPA treatment. NO 2 and NO have the capacity to damage bacterial cells on different levels (DNA, proteins and lipids), and it seems that the hydrophobic part of the membranes could favor the reactive activity of RNS with other molecules ( Chautrand et al, 2022 ). Lipids are a major target for reactive species ( Cabiscol Català, Tamarit Sumalla et al, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…This step of lettuce preparation also has the potential to reduce the bacterial load. Different studies show that non-thermal physical plasma could reduce the microbial load on different abiotic and biotic surfaces due to its ingredients (RNOS) and UV, which damage microbial cells on different levels ( Ehlbeck et al, 2010 ; Handorf et al, 2020a , Handorf et al, 2020b ; Chautrand et al, 2022 ). Some foods cannot be treated with water-based techniques (such as spices, tea and herbs) because it negatively affects their shelf life and quality.…”
Section: Introductionmentioning
confidence: 99%
“…Although the effects of oxidative and nitrosative stress on peptidoglycan are poorly understood, a few studies reported links between oxidative or nitrosative stress and proteins associated with peptidoglycan or its synthesis [ 67 , 68 , 69 , 70 ]. The clearest demonstrated effect of oxidative stress on peptidoglycan comes from a recent study by Giacomucci et al This study showed that the absence of the protein ElyC of unknown function induces the overproduction of OH • in the periplasm, which leads to a direct or indirect interruption of peptidoglycan synthesis [ 71 ].…”
Section: Reactive Oxygen and Nitrogen Species: A Complex Reactions Ne...mentioning
confidence: 99%